Chemical and Biochemical Engineering Approaches in Manufacturing Polyhydroxyalkanoate (PHA) Biopolyesters of Tailored Structure with Focus on the Diversity of Building Blocks - M. Koller (Chemical and Biochemical Engineering Quarterly, 2019)
Polyhydroxyalkanoates (PHA) constitute prokaryotic storage materials not only harnessing microbial cells with benefits for survival under challenging environmental conditions, but also attracting attention as biological materials with properties resembling those of currently used thermoplasts and elastomers of petrochemical origin. Strongly dependent on their monomeric composition and microstructure, PHA´s exact material properties are predestined in statu nascendi, hence, during their biosynthesis. The present review sheds light on established and emerging strategies to produce differently composed PHA homo-, co-, ter-, and quarterpolyesters from the groups of short-, medium-, and long-chain PHA. It is shown how microbial strain selection, sophisticated genetic strain engineering based on synthetic biology approaches, advanced feeding strategies, and smart process engineering can be implemented to generate PHA of tailored monomeric composition, microstructure, molar mass, and molar mass distribution. Tailoring these parameters offers the possibility to produce customer-oriented PHA for various purposes, such as packaging materials, carriers of pharmaceutically active compounds, implants, or other emerging fields of use.